PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN BAHASA INDONESIA MATERI TEKS BACAAN UNTUK MENINGKATKAN MINAT BACA DAN HASIL BELAJAR SISWA PADA SISWA KELAS III DI SDN MARUYUNG II - Sukaenah, Lilis; Ece Sukmana,; Royani, Nia (Sebelas April Elementary Education, 2024)
This study aims to analyze the impact of using audiovisual media in Indonesian language learning on reading interest and learning outcomes of third-grade students at SDN Maruyung II, Tanjungsari District, Sumedang Regency, for the 2023/2024 academic year. The background of this research is the low reading interest and language skills of students. The method used is Classroom Action Research (CAR) with two cycles, which includes planning, action, observation, and reflection. Data were collected through observation, written tests, and interviews. The results show that the use of audiovisual media significantly increases students' reading interest, from 19% in Cycle I to 73% in Cycle II. Additionally, students' learning outcomes also improved, with the average score rising from 67.6 in the initial data to 90 in Cycle II, and the percentage of completeness increasing from 32% to 93%. This study demonstrates that audiovisual media is effective in creating an engaging and interactive learning experience, encouraging students to be more active and involved in the learning process. It is recommended that teachers continue to implement innovative teaching media to enhance student engagement and learning outcomes.